Children in Digital Age – European Union and Central European Best Practices and Challenges - Baracsi, Katalin (Children in Digital Age, 2025)
Abstract:This chapter delves into the crucial issue of child protection in the digital age, examining the landscape in both the European Union and Central European regions. The narrative unfolds through the lens of the author’s 16-year experience conducting interactive sessions on safe internet use for various age groups. Despite the pervasive influence of technology, some individuals resist internet adoption, even for their children. Moreover, the chapter underscores the dual nature of the Internet, presenting both opportunities for legitimate users and risks from criminal activities. The primary focus of the chapter is to scrutinise existing child protection legislation, institutions, and authorities in the context of online safety. The analysis employs a blend of theoretical and practical approaches, utilising a diverse range of sources, particularly from the online realm. The chapter explores gaps in the legal framework and institutional background, aiming to identify areas for improvement. Keywords: child online protection, online risks, digital media literacy, cybersecurity, children and youth safety